Ionizing radiation and photodynamic therapy lead to multimodal tumor cell death, synergistic cytotoxicity and immune cell invasion in human bladder cancer organoids - Annabell Reinhold; Annegret Glasow; Sandra Nürnberger; Annett Weimann; Lucie Telemann; Jens-Uwe Stolzenburg; Jochen Neuhaus; Mandy Berndt-Paetz (Photodiagnosis and Photodynamic Therapy)
Background: Photodynamic therapy (PDT) and radiotherapy using ionizing radiation (IR) are promising options for organ-preserving treatment of bladder cancer (BCa). A combination therapy (IR+PDT) could be beneficial for BCa treatment. Purpose: For PDT, we used the near-infrared photosensitizer tetrahydroporphyrin-tetratosylate (THPTS) showing high therapeutic efficacy. Treatment responses were analyzed in BCa organoids. Methods: Organoids consisting of BCa cells lines, bladder fibroblasts and muscle cells were treated with IR (9 Gy) and/or PDT using THPTS (25, 50 μM; 20 J/cm2). Cytotoxicity was determined by microscopy, cell-based assays and histology. The cell death mode was analyzed by applying specific inhibitors followed by immunofluorescence or qPCR analyses of cell death markers. A matrix-based co-culture model was used to study T cell migration into the environment of treated organoids. Results: PDT and/or IR resulted in concentration-dependent reduction of metabolic activity, organoid diameter and integrity. Higher cytotoxicity of IR+PDT vs. monotherapies was observed after 72 h. Non-malignant organoids showed no cytotoxic effects. While apoptosis, necroptosis and ferroptosis were clearly involved in cell death of T-24 cells, cytotoxicity in RT-112 cells was probably provoked by apoptosis, ferroptosis and pyroptosis. IR+PDT resulted in significant migration of Jurkat cells into ECM-embedded organoids within 3 days after treatment. Conclusion: Treatment with IR+PDT showed tumor-selective cytotoxicity with additive or synergistic effects in BCa organoids. Thereby, IR+PDT led to multimodal cell death depending on the cellular context. Migration of T cells into the organoid environment illustrates the immunogenic potential of IR+PDT. Therefore, it might be a promising approach for organ-preserving BCa treatment.